Familial aggregation of multiple sclerosis: Results from the national registry of the disease in Saudi Arabia. Issue 4 (October 2020) - AlJumah, Mohammed; Otaibi, Hessa Al; Al Towaijri, Ghada; Hassan, Ahmed; Kareem, Abid; Kalakatawi, Mamdouh; Alrajeh, Saad; Al Mejally, Mousa; Algahtani, Hussein; Almubarak, Ali; Alawi, Sadaga; Qureshi, Shireen; et al.
Background: Multiple Sclerosis (MS) is a chronic CNS inflammatory disease commonly affecting young adults. Both genetics and environmental factors have been reported to have a role in pathophysiology of the disease. Objective: This article aims to report familial nature and aspects of MS in Saudi Arabia. Method: The study utilized data collected by the National Saudi MS Registry between 2015 and 2018; especially data relevant to the familial history of MS. SPSS 22 was used for all analysis and reporting. Statistical significance was set at p-value < 0.05. Results: The registry included 20 hospitals and a total of 2516 patients from the different regions of Saudi Arabia with median age 32.00 (Range: 11–63) and 66.5% being female. About 12.8% of all registered patients reported a family history of MS (95%CI: 11.2-13.9). Reported parental consanguinity was significantly higher among patients with family history (FMS) (56.3%) compared to non-FMS patients (27.9%). 42.53% of FMS patients reported having siblings affected with MS (95%CI: 37.01–48.21), with more female siblings affected than males (63.4% vs 36.6% respectively). Conclusion: Our Findings suggested that FMS was less prevalent than what was reported previously; however, parental consanguinity was significantly more prevalent among FMS patients than non-FMS. Our findings were in line with those reported in recent studies in the region, but lower than those reported by western countries indicating that increasing prevalence of MS in Saudi Arabia could be multifactorial and other environmental factors should be considered for understanding this recent rise in the prevalence of MS in Saudi Arabia.